Assessment of heterogeneity between European Populations: a Baltic and Danish replication case-control study of SNPs from a recent European ulcerative colitis genome wide association study - Jonaitis Laimas; Vogel Ulla; Krarup Henrik B; Jacobsen Bent A; Kupcinskas Limas; Sventoraityte Jurgita; Ernst Anja; Andersen Vibeke; Denapiene Goda; Kiudelis Gediminas; Balschun Tobias; Franke Andre (BMC, 2011)
Abstract Background Differences in the genetic architecture of inflammatory bowel disease between different European countries and ethnicities have previously been reported. In the present study, we wanted to assess the role of 11 newly identified UC risk variants, derived from a recent European UC genome wide association study (GWAS) (Franke et al., 2010), for 1) association with UC in the Nordic countries, 2) for population heterogeneity between the Nordic countries and the rest of Europe, and, 3) eventually, to drive some of the previous findings towards overall genome-wide significance. Methods Eleven SNPs were replicated in a Danish sample consisting of 560 UC patients and 796 controls and nine missing SNPs of the German GWAS study were successfully genotyped in the Baltic sample comprising 441 UC cases and 1156 controls. The independent replication data was then jointly analysed with the original data and systematic comparisons of the findings between ethnicities were made. Pearson's χ2, Breslow-Day (BD) and Cochran-Mantel-Haenszel (CMH) tests were used for association analyses and heterogeneity testing. Results The rs5771069 (IL17REL) SNP was not associated with UC in the Danish panel. The rs5771069 (IL17REL) SNP was significantly associated with UC in the combined Baltic, Danish and Norwegian UC study sample driven by the Norwegian panel (OR = 0.89, 95% CI: 0.79-0.98, P = 0.02). No association was found between rs7809799 (SMURF1/KPNA7) and UC (OR = 1.20, 95% CI: 0.95-1.52, P = 0.10) or between UC and all other remaining SNPs. We had 94% chance of detecting an association for rs7809799 (SMURF1/KPNA7) in the combined replication sample, whereas the power were 55% or lower for the remaining SNPs. Statistically significant PBD was found for OR heterogeneity between the combined Baltic, Danish, and Norwegian panel versus the combined German, British, Belgian, and Greek panel (rs7520292 (P = 0.001), rs12518307 (P = 0.007), and rs2395609 (TCP11) (P = 0.01), respectively). No SNP reached genome-wide significance in the combined analyses of all the panels. Conclusions This replication study supports an important role for the studied rs5771069 (IL17REL) SNP, but not for rs7809799 (SMURF1/KPNA7), in UC etiology in the Danish, Baltic, and Norwegian populations. Significant genetic heterogeneity was suggested for rs7520292, rs12518307, and rs2395609 (TCP11) in UC etiology between the Nordic and the other European populations.